The Evolution of European Union Development Cooperation Policy towards Sub-Saharan Africa: Achievements and Challenges - Asligül Sarıkamış Kaya (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
This article examines the evolution of the  European Union's(EU) development aid policy towards sub-Saharan Africa since the 2000s by looking at its main achievements and challenges.  As a leading donor of world politics, the EU provides development and humanitarian aid to African countries since the early period of European integration. In addition to aid provision,  the EU is one of main trading partner of African countries. Over the past two decades, the Union development cooperation policy has undergone significant changes. Politically, it strengthened political conditionalities and expanded the role of civil society in development policy. Economically, it shifted from reciprocal trade preferences to non-reciprocal trade preferences.  It introduced performance-based aid allocations in aid management. With these changes, the Union removed the peculiar characteristics of EU development cooperation policy and followed global trends in its development cooperation policy.